Data analysis for relevance of the physical training application - Ruzhitskyi, S. V. (ХНУРЕ, 2024)
Main goal of this work is to explore the data on people's physical activity, as a result of the research we should draw a conclusion about the relevance of developing a system for collecting and providing access to physical training programs. The dataset which was been used during the research was given from the Behavioral Risk Factor Surveillance System. From dataset was taken all necessary data to the research and was used to make some analyses and visualization of this data. According to the resalts of the research was given a conclusion about expediency of creation collecting and providing system.
Keywords: data analysis; physical training